Hyperspectral aerosol optical depths from TCAP flights. Issue 21 (13th November 2013) - Shinozuka, Y.; Johnson, R. R.; Flynn, C. J.; Russell, P. B.; Schmid, B.; Redemann, J.; Dunagan, S. E.; Kluzek, C. D.; Hubbe, J. M.; Segal‐Rosenheimer, M.; Livingston, J. M.; Eck, T. F.; et al.
Abstract [1] The 4STAR (Spectrometer for Sky‐Scanning, Sun‐Tracking Atmospheric Research), a hyperspectral airborne Sun photometer, acquired aerosol optical depths (AOD) at 1 Hz during all July 2012 flights of the Two‐Column Aerosol Project. Root‐mean‐square differences from Aerosol Robotic Network ground‐based observations were 0.01 at wavelengths between 500–1020 nm, 0.02 at 380 and 1640 nm, and 0.03 at 440 nm in four clear‐sky fly‐over events, and similar in ground side‐by‐side comparisons. Changes in the above‐aircraft AOD across 3 km deep spirals were typically consistent with integrals of coincident in situ (on Department of Energy Gulfstream 1 with 4STAR) and lidar (on NASA B200) extinction measurements within 0.01, 0.03, 0.01, 0.02, 0.02, and 0.02 at 355, 450, 532, 550, 700, and 1064 nm, respectively, despite atmospheric variations and combined measurement uncertainties. Finer vertical differentials of the 4STAR measurements matched the in situ ambient extinction profile within 14% for one homogeneous column. For the AOD observed between 350 and 1660 nm, excluding strong water vapor and oxygen absorption bands, estimated uncertainties were 0.01 and dominated by (then) unpredictable throughput changes, up to ±0.8%, of the fiber optic rotary joint. The favorable intercomparisons herald 4STAR's spatially resolved high‐frequency hyperspectral products as a reliable tool for climate studies and satellite validation.